Lapak Jeneponto: Designing an Inclusive Mobile Marketplace UI for MSMEs in Rural Indonesia - Suci Ramadhani Arifin; Sriwahyuningsih Piu (Universitas Islam Negeri Imam Bonjol Padang, 2025)
Jeneponto Regency's MSMEs face significant challenges accessing wider markets despite their economic potential. This research designed a User Interface (UI) for a mobile marketplace application (